Todd LeVasseur and Anna Peterson (eds.), Religion and the Ecological Crisis: The 'Lynn White Thesis' at Fifty. (22nd February 2019) - Veldman, Robin
Abstract : Todd LeVasseur and Anna Peterson (eds.), Religion and the Ecological Crisis: The 'Lynn White Thesis' at Fifty (New York and London: Routledge, 2017), 205 pp., $140.00 (hbk), ISBN: 978-1-138-64412-0.